Cross-flow vortex induced vibrations of inclined helically straked circular cylinders: An experimental study. (November 2015) - Zeinoddini, M.; Farhangmehr, A.; Seif, M.S.; Zandi, A.P.
Abstract: Effects of suppression devices on the vortex induced vibration (VIV) of inclined cylinders appear not to have received previous due attentions. The current paper reports the results of some towing tank experiments on the vortex induced cross-flow vibrations of bare and helically straked cylinders in vertical and inclined arrangements. Rigid test cylinders were mounted on a single degree of freedom elastic support. The inclination angles examined were θ =0°, ±20° and ±45°. The Reynolds number ranged from 4000 to 45 000 and the reduced velocity from 1 to 16. With all tests the mass ratio and the mass-damping parameters were kept constant. Test results on "inclined bare" and "inclined helically straked" cylinders showed that the peak amplitude of the cross-flow oscillations decreased as the inclination angle increased. The suppression ratio remained almost the same with the vertical and inclined cylinders. The validity of the so called "Independence Principle" (IP) was also examined against the test data obtained in the current study. The IP, to some degrees, was valid in the case of "inclined bare" cylinders. In the case of "inclined helically straked" cylinders, the IP outcomes were almost entirely inconsistent with actual test data. In addition, the up- and downstream effects on the VIV response of the inclined bare and helically straked cylinders were discussed. Hilbert Transform of the VIV responses showed that it was able to efficiently discriminate signals belonging to the lock-in, initial and lower branches of the response. Highlights: In-water small scale towing-tank experiments in a uniform flow were conducted. Effects of helical strakes on the dynamics of the VIV in inclined cylinders were studied. The suppression ratio remained almost the same with different inclination angles. The "Independence Principle" (IP), was partly valid in the case of bare cylinders. The IP was almost entirely invalid in the case of helically straked cylinders.